Libraries, books, and collectors of texts.
1 online resource (266 pages)
Keywords: This book presents the collectors’ roles as prominently as the collections of books and texts which they assembled. Contributors explore the activities and networks shaping a range of continental and transcontinental European public and private collections during the Renaissance, Enlightenment and modern eras. They study the impact of class, geographical location and specific cultural contexts on the gathering and use of printed and handwritten texts and other printed artefacts. The volume explores the social dimension of book collecting, and considers how practices of collecting developed during these periods of profound cultural, social and political change.